Quality management initiatives in open and distance learning university - Fatimah Ibrahim (2008)
As an open and distance learning institution, the Open University Malaysia (OUM) needs to ensure that it offers quality services to its learners. A Quality Management System (QMS) was thus established by the Centre for Quality Management and Research & Innovation (CQMRI). The paper describes the initiatives taken to establish the QMS and will detail the Internal Quality Audit process. In addition, it will describe the challenges faced by OUM in managing the four ISO 9001:2000 certified units. IQA determines the governance and control structure in a Quality Management System. The effectiveness of the IQA processes and procedures will be shared. It was found that the introduction of the internal quality audit programmes has increased the level of quality awareness amongst the staff through the internal auditor as an agent. Interviews with the heads and management representatives of the units were conducted to determine the challenges. The findings are expected to be useful to other institutions who are implementing the Quality Management System. (Authors' abstract)